АНГЛІЙСЬКІ ТА УКРАЇНСЬКІ ПАРЕМІЇ: ЕТНОКУЛЬТУРНИЙ АСПЕКТ (Zaporizhzhia Historical Review, 2021)
The article is devoted to the analysis of English and Ukrainian paremii in ethno-cultural aspect. Besides, it clarifies the difference of English and Ukrainian speakers’ attitude towards some categories of the communicative behavior: maxims of its quality, quantity, manner, initiative, silence, etc. The comparative analysis is done on the basis of some English and Ukrainian proverbs and sayings. Difficulties of translation are revealed.